Clinical, Pathological and Molecular Findings in Caprine Arthritis - Encephalitis Virus Infection in Damascus Goats - Eroksuz, Yesari; Timurkan, Mehmet Ozkan; Karabulut, Burak; Incili, Canan Akdeniz; Baydar, Ersoy; Cevik, Aydin; Eroksuz, Hatice (Sciendo, 2022)
Caprine Arthritis-Encephalitis Virus Infection was presented with clinical, pathological, and molecular findings in dairy goats from a breeding unit in Turkey. According to history, 50 of 700 goats and kids showed the clinical signs including anorexia, mastitis, swelling of the joints, lameness, dyspnea and head pressing in the past 2 months. Fifteen and 6 animals were examined clinically and pathologically, respectively. Clinical examination revealed depression, weakness, pneumonia, ataxia and paresis in 15 goats. Histological lesions were composed by a varying degree of interstitial pneumonia, nonsuppurative leukoencephalomyelitis, interstitial nephritis and interstitial myocarditis. Immunohistochemical examinations showed the presence of viral antigen in tubular epithelium, in glial cells and macrophages. In conclusion, this is the first report documenting pathological and molecular changes of Caprine Arthritis-Encephalitis Virus Infection in Turkey in goats.
KLINI?KI, PATOLOŠKI I MOLEKULARNI NALAZI TOKOM INFEKCIJE VIRUSOM ARTRITISA I ENCEFALITISA KOD DAMASCUS KOZA
Keywords: Caprine Arthritis Encephalitis Virus; ELISA; goat; histopathology; PCR